Bouncer service work: emotional labour and flexible masculinity. Issue 1 (13th August 2019) - Søgaard, Thomas Friis; Krause-Jensen, Jakob
Abstract : Purpose: The purpose of this paper is to explore how new policies and standards to professionalise nightclub bouncing along with customer-oriented service imperatives affect bouncers' work practices and identities. Design/methodology/approach: The paper is based on 13 months of ethnographic fieldwork among Danish bouncers and uses the concept of "emotional labour" and related ideas of "interactive service work" to explore how service imperatives play out at political/commercial and organisational levels and how such initiatives are negotiated by bouncers in their work practices. Findings: Until recently, the nocturnal work of bouncers had been relatively unaffected by labour market service paradigms. This is now changing, as policy initiatives and the capitalist service economy colonise ever greater domains of the urban night and the work conducted here. We argue that trends towards professionalisation have landed bouncers in a double-bind situation, in which they are increasingly faced with competing and sometimes contradictory occupational imperatives requiring them both to "front up" effectively to unruly patrons and to project a service-oriented persona. We show how bouncers seek to cope with this precarious position by adopting a variety of strategies, such as resistance, partial acceptance and cultural re-interpretations of service roles. Originality/value: While existing research on nightclub bouncers has primarily focussed on bouncers' physical regulation of unruly guests, this paper provides a theoretical framework for understanding current policy ambitions to "domesticate" bouncers and shows how attempts to construct bouncers as civilised "service workers" is fraught with paradoxes and ambiguities.